2020
DOI: 10.1002/alr.22644
|View full text |Cite
|
Sign up to set email alerts
|

Suction mitigation of airborne particulate generated during sinonasal drilling and cautery

Abstract: Background Coronavirus disease COVID-has significantly impacted endonasal surgery and recent experimentation has demonstrated that sinonasal drilling and cautery have significant propensity for airborne particulate generation immediately adjacent to the surgical field In the present investigation we assessed nasopharyngeal suctioning as a mitigation strategy to decrease particulate spread during simulated endonasal surgical activity Methods Airborne particulate generation in the-μm toμm range was quantified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(71 citation statements)
references
References 18 publications
2
69
0
Order By: Relevance
“…While it is well known that smoke evacuation systems are effective at aerosol and infection mitigation [ 27 ], this novel demonstration of its efficacy in the setting of craniomaxillofacial trauma highlights its usefulness during this era of heightened concern for aerosolization of SARS-CoV-2. Moreover, this finding further complements the growing literature of suction devices mitigating aerosol generation [ 11 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…While it is well known that smoke evacuation systems are effective at aerosol and infection mitigation [ 27 ], this novel demonstration of its efficacy in the setting of craniomaxillofacial trauma highlights its usefulness during this era of heightened concern for aerosolization of SARS-CoV-2. Moreover, this finding further complements the growing literature of suction devices mitigating aerosol generation [ 11 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 77%
“…However, an overall lack of objective data has impeded decision making on key topics including PPE recommendations and pre-procedural COVID-19 testing. While aerosol and droplet generation has been demonstrated from other head and neck procedures in areas such as endonasal and otologic surgery [ 11 , [17] , [18] , [19] , 21 ], there is little published data on the treatment of facial trauma. This is a key knowledge gap as surgical fixation of facial fractures often requires interaction with the same mucosal surfaces in the oral and nasal cavity which have been demonstrated to harbor high viral loads in infected patients [ 8 ], and surgeries often cannot be deferred to allow viral infections to clear [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This solution was only tested on a cadaver model, which may not adequately capture real-life aerosolization as it does not account for the air flow rates in the local environment. 18 , 19 In other cadaver experiments, Workman et al 51 found that the use of nasopharyngeal suctioning via a rigid suction in the contralateral nostril minimizes airborne particulate spread during simulated sinonasal drilling and cautery.…”
Section: Discussionmentioning
confidence: 98%
“… Nasopharyngeal suctioning via rigid suction placed in the contralateral nostril to limit particulate spread during sinonasal drilling. Workman AD, Xiao R, Feng A, et al 51 Preclinical evaluation of intervention: comparison Level 4 (case-control simulation) Risk of Bias: Moderate(cadaver study and lab setting may not accurately reflect in vivo OR conditions) These studies were conducted in the cadaver model. Suctioning is effective in reducing aerosol contamination.…”
Section: Methodsmentioning
confidence: 99%